(The effect of your questions and my answers strategy among fifth-grade primary school students in their science subject and reflective thinking) (Journal of the College of Basic Education, 2024)
The current research aims to identify the effect of the “Your Questions and My Answers” strategy among fifth-grade primary school students in science and their reflective thinking. In of the research objective, the researcher formulated the following null hypothesis: “There is no statistically significant difference at the level (0.05) between the average scores of the students in the experimental group who will study the science subject according to the strategy of your questions and my answers and the average scores of the control group students who will study the same subject in the normal way in the test.” Reflective thinking. An experimental design with two experimental and control groups with a post-test for achievement and reflective thinking was chosen. To achieve the goal of the research, a purposive sample consisting of (62) students was chosen and distributed among the two research groups. The number of students in the experimental group reached (30) students and the number of students in the control group reached (30) students. 32) students, and parity was conducted between the students of the two research groups with the following variables: (chronological age calculated in months, previous information test, previous achievement in science, Raven’s intelligence test, reflective thinking) in the first semester of the academic year (2023-2024), as The researcher determined the academic material that would be taught during the experiment, which amounts to six chapters from the science textbook for the fifth grade of primary school. The researcher formulated behavioral objectives for the topics to be studied. There were (209) behavioral objectives according to Bloom’s levels (remembering, understanding, application). The researcher prepared (48) plans. A daily journal for teaching the two research groups and presenting a model of it to a group of arbitrators to determine its validity and suitability for fifth-grade primary school students. To achieve the goal of the research, the researcher prepared the research tool, the reflective thinking test: it consists of (five skills) with (6) items for each skill. The apparent validity was extracted from During its presentation to a group of arbitrators in education and science teaching methods, its apparent validity was extracted by presenting it to a group of arbitrators in education and science teaching methods. Content validity was also extracted in light of the test’s conformity to the content studied, and the power of distinction, the difficulty factor, and the effectiveness of the incorrect alternatives were also calculated. For each item of the test, using appropriate statistical methods, reliability was extracted using the split-half method, and it reached (0.83) before correction and after correction (0.91). As for the Keuder-Richardson20 method, it reached (0.87). The results resulted in superiority of the experimental group that was studied. By using the strategy of your questions and my answers to the control group that studied in the usual way in the reflective thinking test, the researcher came up with a number of recommendations and proposals that were mentioned in Chapter Four.